2016
DOI: 10.1155/2016/7296092
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1/3 Activation by Resveratrol Attenuates Acute Kidney Injury in a Septic Rat Model

Abstract: Sepsis often results in damage to multiple organ systems, possibly due to severe mitochondrial dysfunction. Two members of the sirtuin family, SIRT1 and SIRT3, have been implicated in the reversal of mitochondrial damage. The aim of this study was to determine the role of SIRT1/3 in acute kidney injury (AKI) following sepsis in a septic rat model. After drug pretreatment and cecal ligation and puncture (CLP) model reproduction in the rats, we performed survival time evaluation and kidney tissue extraction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 29 publications
7
116
0
Order By: Relevance
“…Increasing evidence has suggested that SIRT1 is implicated in renal physiology and pathology, and plays a renal protective role against inflammatory injury [ 31 ]. For example, Xu et al reported that SIRT1/3 activation by resveratrol attenuated AKI following sepsis in a septic rat model [ 32 ]. Wang et al uncovered that resveratrol, a SIRT1 activator, ameliorated the renal tubular injury induced by hyperglycemia both in vitro and in vivo via suppressing apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that SIRT1 is implicated in renal physiology and pathology, and plays a renal protective role against inflammatory injury [ 31 ]. For example, Xu et al reported that SIRT1/3 activation by resveratrol attenuated AKI following sepsis in a septic rat model [ 32 ]. Wang et al uncovered that resveratrol, a SIRT1 activator, ameliorated the renal tubular injury induced by hyperglycemia both in vitro and in vivo via suppressing apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MD plays an important role in several diseases, including AKI [19,29,30]. Additionally, MD is often associated with the triggering of mitophagy pathways, which eliminate dysfunctional or impaired mitochondria [6,31].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis was induced by caecal ligation and puncture (CLP). As previously described [19], a midline incision was made with minimal dissection, and caecal ligation was performed just below the ileocaecal valve to maintain intestinal continuity. Then, a 7-gauge needle was used to make a single perforation in the caecum, which was gently pressed until all the faeces were drained.…”
Section: Establishment Of a Sepsis Model By Caecal Ligation And Puncturementioning
confidence: 99%
“…mitochondria apoptosis in cardiomyocytes 35 and acute kidney injury in a septic rat model, 36 which is also reversed by EX527. The reason for RES and EX527 modulating protein expression of SIRT1 may be that RES (►Fig.…”
Section: Discussionmentioning
confidence: 98%